The effect of a nutritional education program on the nutritional status of elderly patients in a long-term care hospital in Jeollanamdo province: health behavior, dietary behavior, nutrition risk level and nutrient intake - Kim, B.H., Chosun University, Gwangju, Republic of Korea; Kim, M.J., Chosun University, Gwangju, Republic of Korea; Lee, Y.N., Korea Health Industry Development Institute, Cheongwon, Republic of Korea (Nutrition research and practice, 2012)
This study was conducted to assess improvements in nutritional status following the application of nutrition education to elderly patients in a long-term care hospital. The study was carried out from January to May 2009, during which a preliminary survey, a pretest, the application of nutrition education, and a post-test were applied in stages. The number of subjects at pretest was 81, and the number of participants included in the final analysis was 61 (18 men, 43 women), all of whom participated in both the nutrition education program and the post-test. The survey consisted of general demographic items, health behaviors, dietary behaviors, the Nutrition Screening Initiative checklist, and nutrient intake assessment (24 hour recall method). The nutrition education program lasted for four weeks. It included a basic education program, provided once a week, and mini-education program, which was offered daily during lunch times. The survey was conducted before and after the education program using the same assessment method, although some items were included only at pretest. When analyzing the changes in elderly patients after the nutritional education program, we found that, among subjective dietary behaviors, self-rated perceptions of health (P less than 0.001) and of depression (P less than 0.001) improved significantly and that dietary behavior scores also improved significantly (P less than 0.001), while nutritional risk levels decreased. In terms of nutrient intake, subjects' intake of energy, protein, fat, carbohydrate, calcium, phosphorus, iron, vitamin A, thiamin, riboflavin, niacin, and vitamin C all increased significantly (P less than 0.001). These results indicated that nutritional education is effective in improving the nutritional status of elderly patients. We hope that the results of this study can be used as preliminary data for establishing guidelines for nutrition management tailored to elderly patients in long-term care hospitals.